The Effect of pH on Methylene Blue Removal Efficiency at Different Ozonation Times - Adhiksana, Arief; Irwan, Muh; Luvita, Veny; Harjanto, Harjanto; Patmawati, Yuli; Megawati, Eka; Vegatama, Meita Rezki; Ulfa, Elis Diana; Maulidyawati, Putri; Julianty, Rachma Sherlyn (Universitas Tribhuwana Tunggadewi Malang, 2026)
The textile industry has experienced growth over time, and methylene blue (MB) is one of the most frequently utilized dyes. Methylene Blue impacts human health in various ways, including causing skin irritation and systemic effects like changes in blood composition. Thus, ozonation is an alternative method for treating MB wastewater. This study aimed to investigate the effects of reaction time and pH conditions on MB degradation through ozonation. Compared with traditional treatment methods, which often result in the production of by-products, ozonation is regarded as a more environmentally sustainable approach for wastewater treatment. In this study, MB was prepared at an initial concentration of 50 mg/L, with a sample volume of 500 mL, at 25°C. The variations included reaction times of 10 and 20 min and pH levels of 3, 5, 7, 9, and 11. Ozonation was performed using an ozone generator with a flow rate of 200 mg/h. The ozonation results were analyzed using a UV-VIS spectrophotometer at a wavelength of 665 nm for MB. The results demonstrated that optimal performance was achieved at a pH of 7 with a reaction time of 20 minutes, resulting in a final concentration of 0.49 mg/L. This corresponded to a significant 99% removal of MB.